Hukum perdata islam : tinjauan pemenenuhan dan putusnya hak dan kewajiban suami istri dalam pandangan hukum perdata dan hukum Islam.: Tinjauan Pemenenuhan dan Putusnya Hak dan Kewajiban Suami Istri Dalam Pandangan Hukum Perdata dan Hukum Islam. - Faradila, Dinda Silvy (Maliki Interdisciplinary Journal, 2024)
Marriage is a very sacred thing in the nationally or religiously. In the state, law of marriage shows the importance of elements of marriage. Violation of rights and obligations in the household it’s getting worse and needs to be overcome by forming the law or constitution as the source of the law to solving problems in the household. In Islam, marriage is a very sacred thing and it’s supposed to happen once in a lifetime, if there was polygamy the husband must do righteousness among his wife. Fulfillment of rights and obligations it’s governed by civil law and Islamic law and neither shall it be forgotten that the households may be quiet and peacefull.